A Model for Teaching, Assessment and Learning in Engineering Education for Working Adults - Lim, Kin Chew; Low, Stephen; Attallah, Samir; Cheang, Philip; LaBoone, Emet (International Journal of Advanced Corporate Learning (iJAC), 2012)
This paper examines the engineering education programs provided by SIM University (UniSIM) especially in the teaching, assessment, and learning for working adults. In terms of engineering education, the paper emphasized the changes brought about especially in areas like blended learning, capstone project, continuous assessment, quality control and working with engineering accreditation bodies like ABET. All these helped to ensure that UniSIM is able to offer a quality engineering education that is comparable to other institutions in the region and can serve as a model for working adults to upgrade themselves.